SAHABAT DIGITAL CILIK: PROGRAM PENGENALAN KEAMANAN DAN ETIKA BERINTERNET UNTUK ANAK-ANAK - Fitri Hardianti; Kamar Zaman; Tedy Syahlan (Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
This community service program aims to introduce internet safety and digital ethics to children in Siak Regency. The community service was conducted at the Siak Regency Regional Library with participants from Sekolah Alam Sahabat Qur'an Siak. The implementation methodology comprised three phases: planning, implementation, and evaluation. During the program execution, the children demonstrated remarkable enthusiasm while listening to the material presentations delivered by the facilitators, accompanied by a hand puppet named Digi. The children received comprehensive materials covering various topics, including internet introduction, digital space hazards, types of personal information, internet safety strategies, and digital ethics. The community service program was successfully implemented, and the partner institution expressed hope that similar programs could be conducted in the future with broader outreach to benefit more children.